Dental Tourism Development Perspectives In Armenia - Tovmasyan, Gayane («Տնտեսագետ» հրատ.)
Dental tourism is a type of medical tourism when patients travel abroad for receiving dental services and treatment. The purpose of dental tourism is to get quality dentistry at a more affordable price and with the use of more modern technologies. Dental tourism is becoming increasingly popular, especially among the population of countries where the cost of dental services is high or their availability is limited. Armenia has high opportunities for dental tourism development. Many tourists come to Armenia for dentistry services. The main methods used in the article are: desk review, interview and SWOT analysis. Based on the interview results among dental tourists, Armenia is a preferable destination for dental tourism based on its affordable prices and high-quality services. The article explores the main issues and prospects for dental tourism promotion in Armenia. Some recommendations were done towards improving marketing, statistical recording, quality of services, processing development programs, creating online med-portal of dental services, applying for international accreditations and certifications etc. Ատամնաբուժական զբոսաշրջությունը բժշկական զբոսաշրջության տեսակ է, երբ զբոսաշրջիկները մեկնում են արտերկիր՝ ստոմատոլոգիական ծառայություններ և բուժում ստանալու նպատակով: Ատամնաբուժական զբոսաշրջության նպատակն է ստանալ որակյալ բուժում ավելի մատչելի գնով և ժամանակակից տեխնոլոգիաների կիրառմամբ։ Стоматологический туризм – это вид медицинского туризма, когда пациенты выезжают за границу для получения стоматологических услуг и лечения. Цель стоматологического туризма – получить качественную стоматологическую помощь по более доступной цене и с использованием более современных технологий.
Keywords: Markets and Competition